Reversible Frustrated Lewis Pair Addition of N-Heterocycles to Unsaturated C–C Bonds - Dornan, Peter K.; Longobardi, Lauren E.; Stephan, Douglas W. (Synlett, 2014)
N-Heterocycle-tethered olefins and alkynes are cyclized by addition of the N-heterocycle and B(C6F5)3 across the unsaturation. This activation is demonstrated to be reversible at high temperatures.
Keywords: frustrated Lewis pairs; olefin activation; borane; N-heterocycles